Hubungan Kadar Profil Lipid dengan Homosistein pada Pasien Dislipidemia di Laboratorium Klinik Prodia Tangerang - Intan Lambang Astrini; Anak Agung Ayu Eka Cahyani; Mardiyah Hayati (Universitas Muhammadiyah Manado, 2025)
Dyslipidemia is one of the causes of coronary heart disease and stroke. Hypercholesterolemia can cause atherosclerosis. In recent years, there has been an independent risk factor that is an important factor in the presence of blood vessel wall abnormalities, namely homocysteine. Increased homocysteine has been shown to increase the risk of cardiovascular disease independently. This study is an observational analytical study using a cross-sectional design with a retrospective approach. The sample used was 33 respondents selected through a total sampling technique The results of the test on the relationship between Lipid Profile and homocysteine using statistical testing methods, namely Spearman's Rho, yielded the following results: there is no significant relationship between Total Cholesterol and homocysteine with a Sig value of 0.791 (>0.05) and a correlation coefficient of 0.048; there is no significant relationship between LDL Cholesterol and homocysteine with a Sig value of 0.272 (>0.05) and a correlation coefficient of -0.197; there is a significant relationship between HDL Cholesterol and homocysteine with a Sig value of 0.004 (<0.05) and a correlation coefficient of -0.487; there is a significant relationship between Triglycerides and Homocysteine with a Sig value of 0.047 (<0.05) and a correlation coefficient of 0.348. The conclusion of this study is that there is a significant relationship between HDL Cholesterol and Triglycerides to homocysteine in patients with Dyslipidemia at Prodia Clinical Laboratory Tangerang. Further research is needed with a larger sample size focusing on the gender and age of the respondents.